The Feasibility of Information Technology Infrastructure according to the Regulation of the Minister of National Education No.40 of 2008: A Case Study at SMK Palembang City - Supriyati Supriyati; Darius Antoni; Muhammad Akbar (International Journal of Information Systems and Informatics, 2020)
The feasibility of infrastructure to determine the level and feasibility of Information Technology Vocational Schools in Palembang City. Based on research according to Permendiknas No. 40 of 2008 contains computer laboratory furniture, including: the ratio of the number of student chairs and desks, the ratio of the number of teacher chairs, computer equipment, and educational media. This research methodology uses quantitative methods, where the data collection method is obtained from a questionnaire of information users as respondents. Data analysis used SPSS version 20 for data processing. The analysis results obtained according to Permendiknas No. 40 of 2008 and referring to O'Brien's theory, namely as follows: SMK Negeri 1, SMK Negeri 2, SMK Negeri 3, SMK Negeri 4, and SMK Negeri 5 Palembang, the achievement in the category is less feasible, namely with an average percentage of 5.6% , while 27.77% with a decent category achievement and 66.7 with very decent category.